ANTISYNTHETASE SYNDROME: A RARE AND CHALLENGING DIAGNOSIS – CASE REPORT AND LITERATURE REVIEW - Karanfilovski, Vlatko; Gjeorgjieva Janev, Olivera; Nanovic, Zorica; Damjanovska Krstikj, LJubinka (Central Medical Library - Bulgaria, 2022)
Antisynthetase syndrome (ASS) is rare idiopathic inflammatory myopathy (IIM) characterized principally by myositis, generally symmetrical arthritis and interstitial lung disease (ILD) in association with serum autoantibodies to aminoacyl-transfer RNA synthetases. More variable features include arthralgia, Raynaud phenomenon, heliotrophic rash, distal esophageal dysmotility and mechanic's hands. In this case report we describe a 46-years old woman who initially presented with arthritis and subtle myositis which delayed the recognition of ASS and contributed for considering the condition as seronegative rheumatoid arthritis for several years. During the next few years, the patient was progressively worsening, with a disability to stand up from a sitting position, gradual onset of exertional dyspnea, difficult-to-control dry cough and thick, hyperkeratotic skin of both hands (mechanic’s hands). This constellation of symptoms was highly suspicious for ASS and additional serological and radiological examinations were done which confirmed the diagnosis. The need for further detailed investigation when an interstitial lung disease overlaps with a known rheumatoid condition is obligatory, as shown in this case. A multidisciplinary evaluation is highly recommended to evaluate the clinical, serological and radiological findings in each patient suspected for ASS in order to establish early diagnosis and timely management.
Keywords: Antisynthetase syndrome (ASS); interstitial lung disease (ILD); mechanic hands; autoantibody